Expression of pro-inflammatory and co-stimulatory molecules on the surface of macrophages in vitro in patients with pulmonary tuberculosis - E. G. Churina; A. V. Sitnikova; O. I. Urazova; V. V. Novitskiy; M. R. Patysheva; P. N. Golubchikov; E. P. Stepanova (Бюллетень сибирской медицины, 2021)
The aim of this study was to identify features of the expression of pro-inflammatory and co-stimulatory molecules on the surface of macrophages in vitro in patients with pulmonary tuberculosis, depending on the clinical form of the disease and sensitivity of the pathogen to anti-TB drugs.Materials and methods. 40 patients (36 men and 4 women) with pulmonary tuberculosis (TB) were examined: 18 patients (16 men and 2 women, average age (44.56 ± 8.10) years) with disseminated tuberculosis (DTB) and  22 patients (20 men and 2 women, average age (46.54 ± 5.24) years) with infiltrative tuberculosis (ITB). Of those, 30 patients secreted Mycobacterium tuberculosis (MBT) sensitive to the basic anti-TB drugs (ATBD), and 10 patients secreted MBT resistant to first-line anti-TB drugs. Venous blood was the study material. To isolate monocytes from the whole blood in order to transform them into macrophages, ficoll density gradient centrifugation with gradient density of 1.077 g/cm3 was used followed by immunomagnetic separation of CD14+ cells. Monocytes were cultured in a complete culture medium X-VIVO 10 with gentamicin and phenol red with the addition of the macrophage colony-stimulating factor (M-CSF) (5 ng/ml) at a concentration of 1×106 cells/ml with the following stimulators: interleukin (IL) 4 (10 ng/ml) and interferon (IFN) γ (100 ng/ml). Immunophenotyping of macrophages was performed using monoclonal antibodies to CD80, CD86, and HLA-DR on a Beckman Coulter CytoFLEX LX flow cytometer (Beckman Coulter, USA). The analysis of the obtained data was carried out using the CytExpert 2.0 software application. The results were analyzed using statistical methods.Results. The number of intact and cytokine-stimulated (IL-4 and IFNγ) CD80-positive macrophages in patients with ITB and drug-resistant TB (DR TB) exceeded their number not only in healthy donors, but also in patients with DTB and drug-sensitive TB (DS TB), respectively. In addition, an increase in CD86 expression on the surface of macrophages was registered in patients with ITB and DR TB after adding IFNγ (M1-activation inducer) to the suspension culture. In contrast, in patients with DTB and DS TB, the number of macrophages with expression of B7 family co-stimulating molecules decreased or remained within the normal values in the absence of a reaction to cytokines during cytokine induction. Deficiency of HLA-DR-positive macrophages was found in all TB patients. The minimal number of macrophages expressing HLA-DR was found in patients with DTB and DS TB after cell incubation with IL-4 (M2-activation inducer).Conclusion. Evaluation of the expression of B7 (CD80/86) and HLA-DR membrane molecules on macrophages in TB patients allows to conclude that anti-TB immune response is impaired at stages of antigen presentation (in all examined patients with TB) and co-stimulation (in DTB and DS TB). An increase in the expression of macrophage surface molecules CD80 (with M1- and M2-stimulation) and CD86 (with M1-stimulation) in patients with ITB and DR TB indicates an increase in cell reactivity in these forms of TB. In addition, deficit of expression of HLA-DR (a key marker of pro-inflammatory cell activation) on the surface of macrophages in TB can be considered as a general (independent of the clinical form of the disease and drug sensitivity of the pathogen) pathogenetic factor of immune imbalance in pulmonary tuberculosis.